Screening of Some Sulfonamide and Sulfonylurea Derivatives as Anti-Alzheimer’s Agents Targeting BACE1 and PPARγ - Ning Li; Yan Wang; Wensheng Li; Haiyan Li; Liu Yang; Jun Wang; Hazem A. Mahdy; Ahmed B. M. Mehany; Dareen A. Jaiash; Eman Y. Santali; Ibrahim H. Eissa (Journal of Chemistry)
In the last few decades, Alzheimer’s disease (AD) has emerged as a serious global problem, and it has been considered as the most common type of dementia. PPARγ and beta-secretase 1 (BACE1) are considered as potential targets for Alzheimer’s disease management. In the same time, sulfonylureas and sulfonamides have been confirmed to have PPARγ agonistic activity. Aiming to obtain new anti-AD agents, thirty-five compounds of sulfonamide and sulfonylurea derivatives having the same essential pharmacophoric features of the reported PPARγ agonists have been subjected to virtual screening. Docking studies revealed that five compounds (1, 2, 3, 4, and 5) have promising affinities to PPARγ. They were also docked into the binding site of BACE1. In addition, ADMET and physicochemical properties of these compounds were considered. Additionally, these compounds were further evaluated against BACE1 and PPARγ. Compound 2 showed IC50 value of 1.64 μM against BACE1 and EC50 value of 0.289 μM against PPARγ.